2000
DOI: 10.1128/iai.68.1.360-367.2000
|View full text |Cite
|
Sign up to set email alerts
|

Isolates ofChlamydia trachomatisThat Occupy Nonfusogenic Inclusions Lack IncA, a Protein Localized to the Inclusion Membrane

Abstract: The chlamydiae are obligate intracellular pathogens that occupy a nonacidified vacuole, termed an inclusion, throughout their developmenal cycle. When an epithelial cell is infected with multiple Chlamydia trachomatis elementary bodies, they are internalized by endocytosis into individual phagosomal vacuoles that eventually fuse to form a single inclusion. In the course of large-scale serotyping studies in which fluorescent antibody staining of infected cells was used, a minority of strains that had an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 26 publications
(14 reference statements)
7
125
3
2
Order By: Relevance
“…Likewise, an IncA-specific monoclonal antibody, when micro-injected into C. trachomatis-infected cells, provokes the development of aberrant multilobed inclusions, similar to those observed in C. psittaci GPIC-infected cells . These independent findings strongly suggest that one of the functions of the IncA protein is to facilitate homotypic vesicle fusion through IncA intermolecular interactions in C. trachomatis-infected cells Suchland et al, 2000).…”
Section: Interaction Of Chlamydia With the Host Cell Cytosolmentioning
confidence: 82%
See 1 more Smart Citation
“…Likewise, an IncA-specific monoclonal antibody, when micro-injected into C. trachomatis-infected cells, provokes the development of aberrant multilobed inclusions, similar to those observed in C. psittaci GPIC-infected cells . These independent findings strongly suggest that one of the functions of the IncA protein is to facilitate homotypic vesicle fusion through IncA intermolecular interactions in C. trachomatis-infected cells Suchland et al, 2000).…”
Section: Interaction Of Chlamydia With the Host Cell Cytosolmentioning
confidence: 82%
“…IncA may therefore subvert signal transduction pathways in the host cell, to the advantage of the pathogen. A recent study has revealed that certain C. trachomatis strains that do not express an IncA homologue also produce uncharacteristic multiple inclusions in single cells (Suchland et al, 2000). Likewise, an IncA-specific monoclonal antibody, when micro-injected into C. trachomatis-infected cells, provokes the development of aberrant multilobed inclusions, similar to those observed in C. psittaci GPIC-infected cells .…”
Section: Interaction Of Chlamydia With the Host Cell Cytosolmentioning
confidence: 92%
“…However, the function of most of these effector proteins has still to be assigned. Clinical C. trachomatis isolates, mutated in the gene encoding the putative TTS effector protein IncA, have been shown to give rise to multiple inclusions after infection with a high MOI in contrast to the single inclusions typically seen in IncA-producing wild-type isolates (21,22). However, intracellular replication of C. trachomatis was not inhibited in the absence of homotypic fusions.…”
Section: -3-3␤ From Decorating Chlamydia-containing Inclusion Bodiesmentioning
confidence: 86%
“…Based on these data, we argue that INP0400 can inhibit TTS in C. trachomatis. It is tempting to suggest that the inhibitory effect of INP0400 on RB multiplication during the chlamydial mid-cycle is due to an inhibited translocation of other TTS effectors than IncA, because incA mutants of C. trachomatis have been found among clinical isolates (21).…”
Section: Discussionmentioning
confidence: 99%
“…4) increased the similarity of this strain to other members of the clade (not shown). These sequences were each closely related to strain D(s)/2923, an IncA-negative isolate collected during the same time period and geographical area as the specimens analysed in this study (Jeffrey et al, 2010;Suchland et al, 2000) (Fig. 4).…”
Section: Mitigating Contamination From Non-chlamydial Dnamentioning
confidence: 99%